THE IMPLICATIONS OF OXIDATIVE STRESS IN LONG-COVID PATHOGENESIS - Ćorić, Vesna (Medicinski podmladak, 2023)
As far as clinical presentation is concerned, following an episode of acute sickness, the SARS-CoV-2 infection may lead to the development of a number of complications known as post-acute sequelae of SARS-CoV-2 infection (PASC). The definition PASC, as well as its estimated prevalence evolved over the course of time and acquired knowledge. Although COVID-19 was initially characterized as an acute respiratory illness, convalescents frequently report diverse clinical manifestations related to several organ systems, referred to as long-COVID. However, the fundamental molecular mechanisms that are responsible for the incapacitating symptoms, occurring in patients with long-COVID, remain largely unexplained at this time. From molecular medicine point of view, one of the proposed postulates favors the impaired redox balance,  that may serve as a central hub responsible for mechanisms disturbing the cellular homeostasis, innate immune response and metabolism. This review will try to tackle the current knowledge about the underlying mechanisms comprising the proposed interplay of the disturbed redox balance and inflammation, that may potentially contribute to the occurrence of tissue or organ damage that is linked with COVID-19, as well as the eventual manifestation of symptoms observed in individuals with long-COVID. One might assume that in certain individuals, there are mechanisms that may dominate over others. Genetic variability may offer some answers, especially in the case of polymorphisms occurring in genes that encode for antioxidant proteins and enzymes.
Keywords: long-COVID; oxidative stress; inflammation; polymorphisms; antioxidant defense